HUBUNGAN BERAT BADAN LAHIR BAYI DENGAN RUPTUR PERINEUM PADA PERSALINAN NORMAL DI KLINIK PRATAMA HAMIDAH TANJUNG MORAWA KAB. DELI SERDANG TAHUN 2023 - Ivansri Marsaulina Panjaitan (Universitas Prima Indonesia, 2023)
Postpartum haemorrhage being the primary cause of maternal mortality. One of the causes of bleeding is a Ruptured Perineum. Ruptured perineum is perlukaan the way birth happens at the time of the birth of the baby is either using or not using the tool. One of the factors cause ruptured perineum is the birth weight. This research aims to know the relationship of weight born babies with ruptured perineum on a vaginal birth at the clinic Pratama Tanjung Morawa Hamida 2023 Type of this research is a survey of the analytic approach of cross sectional. The sample in this research is the normal maternity mother who suffered a ruptured perineum clinic Pratama Tanjung Morawa Hamida in January-July 2023 i.e. 64 people. This study uses secondary data, namely data obtained from clinics Pratama Hamida by taking the results of medical record data on maternal birthing normally experiencing ruptured perineum and the weight of the baby to be born. The results showed that from 64 respondents (100%) the normal maternity examined birth weight < 2500 grams happens ruptured perineum 0 (0%) respondents and birth weight of 2500-4000 grams of as much as 42 respondents (65,6%) with a ruptured perineum thirteen respondents (20.3%) which is not ruptured by as much as 29 respondents (45,3%) while the weight born > 4000 as many as 21 respondents (32.8%) who experienced a ruptured with as many as 20 respondents (31.3%) and not ruptured by as much as 1 respondents (1.6%). Based on the results of the test statistic chi-square obtained results i.e. p = 0.000 where p-value < 0.05. Conclusions in this study demonstrate that there is a significant relationship between birth weight infant with a ruptured perineum. For that health workers are expected to provide guidance as well as encourage pregnant women to do gymnastics pregnant in order to Flex the muscles of perineum walls to reduce cases of ruptured perineum.